Economic Policy Uncertainty and Exchange Market Pressure: Panel Evidence - Gilal, Muhammad Akram; Nizamani, Abdul Rehman; Khushik, Ali Gul; Gilal, Ashfaque Ali (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
Controlling for macroeconomic indicators and trade openness, this study examined the impact of economic policy uncertainty on exchange market pressure for a panel of 25 countries from 2003Q2 to 2021Q3. The pooled mean group estimator, which allows for variation in short-run estimates and error variances but constrains long-run parameters to be the same, was employed to conduct the analysis. The overall panel was further split into developed, developing, and emerging economies panels to check if there was variation in the effect of economic policy uncertainty. Further, we split the entire sample into pre and post-GFC period to account for potential nonlinearity caused by the structural break (i.e., global financial crisis). Results indicate significant positive effect of economic policy uncertainty on EMP1. Economic policy uncertainty has larger impact on developing and emerging economies EMP1 than their developed counterparts entire sample period and all countries panel all sample periods. For EMP2 economic policy uncertainty has significant effect only for developing and emerging economies entire sample period. Furthermore, the effect of uncertainty in economic policy on EMP1 is larger in pre-GFC period than post-GFC period for all countries and developed economies panel. For developing and emerging economies, post-GFC is larger than pre-GFC period. All the remaining variables have mixed effect on either of the exchange market pressure indexes.